Odor-free environment-friendly sand-containing fog sealing layer and preparation method thereof
By using a clean and environmentally friendly sand-containing mist seal on asphalt pavement, the poor control effect of the flue gas release amount and driving safety of asphalt pavement in the prior art has been solved, and the effect of effectively suppressing the flue gas release and extending the service life of the pavement is achieved.
Patent Information
- Application Number
- CN202311359798.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art has limited effect when reducing the amount of smoke released on asphalt pavement and may affect driving safety. The road surface is prone to cracking and particle loss under high temperature sunlight.
It adopts a clean and environmentally friendly sand-containing mist sealing layer, which consists of asphalt, water, composite emulsifier, defoaming agent, latex, suspension agent, fine sand particles and clean and environmentally friendly microcapsules. The composite shell material of the pure and environmentally friendly microcapsules includes inorganic base shell/nanotomarine/polydopamine, the core material contains odorant, and the shell surface is loaded with metal chelates.
This technology can not only effectively suppress the amount of pollutants generated by high temperature sun exposure on asphalt pavement and reduce the release of smoke, but also avoid oil on the road surface due to the slow release effect of microcapsules, improve driving safety, and extend the service life of the road surface.
Smart Images

Figure CN119859033A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of special asphalt, and specifically relates to a odorless and environmentally friendly sand-containing fog seal layer and a preparation method thereof. Background Art
[0002] With the rapid development of China's road engineering technology, asphalt pavement has been basically popularized throughout the country. However, due to the long-term exposure of asphalt pavement in some areas to strong sunlight, the temperature of dark brown or black asphalt will rise significantly, resulting in problems such as cracking, falling particles, and releasing pungent odors. These problems not only reduce the service life of the pavement, but also affect human health.
[0003] CN116285687A discloses a phase-change mist seal material containing phase-change material, and its preparation method and application. The method directly mixes the phase-change material into the mist seal, and while repairing the road surface damage, reduces the road surface temperature by means of the phase-change heat absorption effect of the phase-change material, further reducing the road surface damage caused by high temperature and the amount of smoke released. However, the mist seal material provided by the method can only passively suppress asphalt smoke, and after being spread on the road surface, the phase-change material contained therein will undergo phase change liquefaction under the action of high temperature, further causing oil spillage on the road surface, affecting driving safety.
[0004] In summary, the main method of reducing smoke emission from asphalt pavement in the existing technology is to reduce the temperature of the pavement to a certain extent. This method has limited effect in reducing smoke and may affect driving safety. Therefore, it is very necessary to develop a pavement repair material that can actively reduce the smoke emission from asphalt pavement without affecting driving safety. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a deodorizing and environmentally friendly sand-containing fog seal and a preparation method thereof. The deodorizing and environmentally friendly sand-containing fog seal of the present invention not only has good road performance, but also can effectively suppress the amount of pollutants generated by asphalt pavement under high temperature and sunlight, providing a new idea for the functional utilization of asphalt materials.
[0006] The first aspect of the present invention provides a odorless and environmentally friendly sand-containing fog sealing layer, wherein the odorless and environmentally friendly sand-containing fog sealing layer comprises the following components in parts by mass:
[0007] Asphalt: 35-70 parts;
[0008] Water: 30-70 parts;
[0009] Composite emulsifier: 2-8 parts;
[0010] Defoaming agent: 0.5-3 parts;
[0011] Latex: 5-30 parts;
[0012] Suspension: 20-40 parts;
[0013] Fine sand: 20-45 parts;
[0014] Odor-free and environmentally friendly microcapsules: 5-40 portions;
[0015] The deodorizing and environmentally friendly microcapsule comprises a composite shell material and a core material, wherein the composite shell material comprises an inorganic base shell / nano-tourmaline / polydopamine, and the core material comprises one or more deodorizing agents; and the surface of the shell material is loaded with a metal chelate.
[0016] Furthermore, the asphalt is commercially available No. 70 or No. 90 base asphalt.
[0017] Furthermore, the composite emulsifier includes a cationic emulsifier and an amphoteric emulsifier, and the mass ratio of the cationic emulsifier to the amphoteric emulsifier is 1:0.5-2.5.
[0018] Further, the cationic emulsifier includes one or more of amine salt type surfactants with a carbon number greater than 8; preferably, one or more of tetradecyl-dimethylpyridinium ammonium bromide, octadecylamide propyl dimethyl dihydroxypropyl ammonium chloride, behenic acid amide propyl dimethyl dihydroxypropyl ammonium chloride, hexadecylamide propyl trimethyl ammonium chloride, dioctadecyl-methylbenzyl ammonium chloride, dodecyldimethylbenzyl ammonium chloride, octadecyldimethylhydroxyethyl quaternary ammonium nitrate, hexadecyltrimethylammonium bromide, and hexadecyltrimethylammonium chloride; further preferably, hexadecyltrimethylammonium bromide.
[0019] Furthermore, the amphoteric emulsifier is a polyol-type surfactant; preferably one or more of fatty acid ethylene glycol esters, monoglycerides, pentaerythritol fatty acid esters, sorbitan fatty acid esters, and sucrose fatty acid esters; more preferably sorbitan fatty acid esters.
[0020] Furthermore, the defoaming agent is one or more of sunflower oil, polydimethylsiloxane, eicosanol, and docosanol.
[0021] Furthermore, the latex is one or more of natural latex, carboxylated styrene-butadiene latex, polyurethane latex, nitrile latex, and chloroprene latex.
[0022] Furthermore, the suspending agent is one or more of bentonite, kaolin, carbon black and talc.
[0023] Furthermore, the particle size of the suspending agent is 800-1800 mesh.
[0024] Furthermore, the fine sand particles are one or more of quartz sand, carborundum, corundum sand or basalt sand.
[0025] Furthermore, the particle size of the fine sand particles is 30-300 mesh; preferably, the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 50%-60%, the mass proportion of sand particles of 70-130 mesh is 20%-30%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 10%-30%.
[0026] Furthermore, the particle size of the odorless and environmentally friendly microcapsules is 1-5 μm.
[0027] Furthermore, the mass ratio of the odorless and environmentally friendly microcapsule composite shell material to the core material is 1:(0.5-2).
[0028] Furthermore, the deodorant is one or more of aldehydes, alcohols, esters, and ketones, and preferably includes aldehydes, alcohols, esters, and ketones at the same time.
[0029] Furthermore, the aldehydes are selected from one or more of aliphatic aldehydes having a carbon number greater than 10 and aromatic aldehydes having a carbon number greater than 7. The aliphatic aldehyde having a carbon number greater than 10 is selected from one or more of 2-methylundecylaldehyde and 10-undecenal; the aromatic aldehyde having a carbon number greater than 7 is selected from one or more of benzaldehyde, cinnamaldehyde, o-methoxy-p-methylbenzaldehyde, 2-methyl-3-(4-isopropylphenyl)propanal, and 2-methyl-3-(3,4-methylenedioxyphenyl)propanal.
[0030] Furthermore, the alcohol is selected from one or more of terpene alcohols with a carbon number greater than 10 and cyclic terpene alcohols with a carbon number greater than 10. The terpene alcohols with a carbon number greater than 10 are selected from one or more of geraniol, linalool, citronellol, ionol, farnesol, myrcene alcohol, lavandulol, and nerolidol; the cyclic terpene alcohols with a carbon number greater than 10 are selected from one or more of menthol, terpineol, isobornyl alcohol, cedarwood alcohol, and santalol.
[0031] Furthermore, the esters are selected from one or more of aromatic esters with carbon atoms greater than 12 and terpene esters with carbon atoms greater than 11. The aromatic esters with carbon atoms greater than 12 are selected from one or more of isoamyl benzoate, benzyl benzoate, isoamyl salicylate, benzyl salicylate, leaf alcohol salicylate, benzyl cinnamate, and phenylethyl cinnamate; the terpene esters with carbon atoms greater than 11 are selected from one or more of geranyl formate, geranyl acetate, geranyl propionate, neryl acetate, linalyl formate, linalyl propionate, lavender acetate, and citronellal butyrate.
[0032] Further, the ketones are selected from one or more of aliphatic ketones with carbon number greater than 3 and cyclic terpene ketones with carbon number greater than 10. The aliphatic ketones with carbon number greater than 3 are selected from one or more of 3-hydroxy-2-butanone, 2,3-butanedione, and 3-pentene-2-one; the cyclic terpene ketones with carbon number greater than 10 are selected from one or more of damascenone, ionone, irone, menthone, and carvone.
[0033] Furthermore, the composite shell material comprises inorganic base shell / nano-tourmaline / polydopamine, wherein the mass ratio of the inorganic base shell to the nano-tourmaline is (1-5):1, and the mass ratio of the inorganic base shell to the polydopamine is 1:(0.1-1).
[0034] Furthermore, the material of the inorganic base shell is selected from one of silicon dioxide and titanium dioxide, preferably silicon dioxide.
[0035] Furthermore, the surface of the composite shell material is loaded with a metal chelate, wherein the metal is preferably copper.
[0036] Furthermore, the surface of the composite shell material is loaded with metal chelates, and the metal loading accounts for 0.1wt%-10wt% of the total mass of the odorless and environmentally friendly microcapsules.
[0037] Furthermore, the method for preparing the odorless and environmentally friendly microcapsules comprises the following steps:
[0038] S1: mixing nano-tourmaline, a surfactant and a solvent, modifying the mixture under stirring, washing the mixture after the modification, and freeze-drying the mixture to obtain modified nano-tourmaline;
[0039] S2: stirring and mixing one or more deodorizing agents to obtain a core material mixed liquid;
[0040] S3: adding a solvent and the modified nano-tourmaline obtained in step S1 to the core material mixed solution obtained in step S2, and stirring and mixing;
[0041] S4: adding an inorganic base shell precursor to the reaction system of step S3, stirring and mixing, and obtaining a Pickering emulsion;
[0042] S5: adjusting the pH value of the Pickering emulsion obtained in step S4 to 3-6, continuing stirring, and then aging, filtering, and freeze-drying to obtain a odorless and environmentally friendly microcapsule matrix;
[0043] S6: dispersing the odorless and environmentally friendly microcapsule matrix obtained in step S5 in a buffer solution, adding dopamine hydrochloride, treating under stirring, and then filtering, washing, and freeze-drying;
[0044] S7: dispersing the solid powder obtained after freeze-drying in step S6 in a metal ion salt-formamide solution, treating under stirring, and after the reaction is completed, filtering, washing, and freeze-drying to obtain odorless and environmentally friendly microcapsules.
[0045] Furthermore, in step S1, the surfactant is a cationic surfactant, preferably at least one of hexadecyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride, and octadecyltrimethylammonium chloride.
[0046] Furthermore, in step S1, the solvent is an aprotic solvent with a boiling point > 100°C, preferably at least one of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide, and more preferably formamide.
[0047] Furthermore, in step S1, the mass ratio of the nano-tourmaline to the surfactant is (1-10):1, and the mass ratio of the solvent to the surfactant is (10-40):1.
[0048] Furthermore, in step S1, the stirring speed is 400-600 rpm; the modification temperature is 100-190° C., and the modification time is 4-8 hours.
[0049] Furthermore, in step S1, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.
[0050] Furthermore, in step S2, the stirring speed is 400-600 rpm, the stirring temperature is 30-70° C., and the stirring time is 3-10 minutes.
[0051] Furthermore, in step S3, the solvent is an aprotic solvent with a boiling point > 100°C, preferably at least one of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide, and more preferably N,N-dimethylformamide.
[0052] Furthermore, in step S3, the mass ratio of the core material mixture to the modified nano-tourmaline is (1-10):1, and the mass ratio of the solvent to the modified nano-tourmaline is (10-40):1.
[0053] Furthermore, in step S3, the stirring speed is 400-600 rpm, the stirring temperature is 30-60° C., and the stirring time is 4-6 hours.
[0054] Furthermore, in step S4, the inorganic base shell precursor is one of a silicate compound and a titanate compound, and is more preferably a silicate compound;
[0055] Furthermore, the silicate compound is preferably one or more of methyl silicate, ethyl orthosilicate, tetraethyl orthosilicate, and butyl orthosilicate, and is more preferably tetraethyl orthosilicate.
[0056] Furthermore, in step S4, the mass ratio of the core material mixture to the inorganic base shell precursor is (0.5-2): 1. The stirring speed is 400-600 rpm, the stirring temperature is 30-60° C., and the stirring time is 4-6 hours.
[0057] Furthermore, in step S5, the pH can be adjusted by using dilute acid, such as dilute hydrochloric acid. The stirring speed is 400-600 rpm, the stirring temperature is 30-60° C., and the stirring time is 4-6 hours.
[0058] Furthermore, in step S5, the aging condition is: standing at 40-60°C for 12-30 hours. The freeze-drying condition is: vacuum drying at a temperature of -40--20°C for 4-8 hours.
[0059] Furthermore, in step S6, the buffer is one or more of phosphate buffer, carbonate buffer, and Tris buffer, preferably Tris buffer.
[0060] Furthermore, in step S6, the pH value of the buffer solution is preferably 8-10.
[0061] Furthermore, in step S6, the mass ratio of the buffer solution to the odorless and environmentally friendly microcapsule matrix obtained in step S5 is (10-100):1.
[0062] Furthermore, in step S6, after adding dopamine hydrochloride, the mass concentration of dopamine in the reaction system is 2-10 mg / mL.
[0063] Furthermore, in step S6, the stirring speed is 100-300 rpm, the stirring temperature is 20-40° C., and the stirring time is 12-24 hours.
[0064] Furthermore, in step S6, the freeze-drying conditions are: vacuum drying at a temperature of -40°C to -20°C for 4-8 hours.
[0065] Furthermore, in step S7, the solid powder obtained after freeze-drying in step S6 is dispersed in a metal ion salt-formamide solution, and ultrasonic dispersion can be used.
[0066] Furthermore, in step S7, the metal ion salt is preferably a copper ion salt, and more preferably anhydrous copper sulfate.
[0067] Furthermore, in step S7, in the metal ion salt-formamide solution, the mass ratio of the metal ion salt to formamide is (0.5-1.5):1.
[0068] Furthermore, in step S7, the mass ratio of the metal ion salt-formamide solution to the solid powder obtained after freeze-drying in step S7 is (5-20):1.
[0069] Furthermore, in step S7, the stirring speed is 200-450 rpm, the treatment temperature is 100-190° C., and the treatment time is 2-5 hours.
[0070] Furthermore, in step S7, the freeze-drying conditions are: vacuum drying at -40°C to -20°C for 4-8h.
[0071] The second aspect of the present invention provides a method for preparing the above-mentioned odorless and environmentally friendly sand-containing fog seal layer, comprising the following steps:
[0072] P1: Preparation of composite emulsifier;
[0073] P2: Stir and mix water and part of the composite emulsifier prepared in step P1, adjust the pH value, and obtain a soap solution;
[0074] P3: After heating the asphalt and the soap solution obtained in step P2 respectively, shearing them to obtain emulsified asphalt;
[0075] P4: Add the remaining part of the composite emulsifier prepared in step P1 to the emulsified asphalt obtained in step P3, and stir to mix;
[0076] P5: Add defoaming agent to the reaction system of step P4 and stir to mix;
[0077] P6: Add a suspending agent to the reaction system of step P5 and stir to mix;
[0078] P7: Add the odorless and environmentally friendly microcapsules to the reaction system of step P6 and stir to mix;
[0079] P8: Add latex to the reaction system in step P7 and stir to mix;
[0080] P9: Add fine sand particles to the reaction system of step P8, stir and mix, and obtain an odorless and environmentally friendly sand-containing fog seal layer.
[0081] Furthermore, in step P1, the preparation of the composite emulsifier is to uniformly mix the cationic emulsifier and the amphoteric emulsifier.
[0082] Furthermore, in step P2, the water is preferably deionized. The mass ratio of the water to the composite emulsifier is: (5-20):1.
[0083] Furthermore, in step P2, the stirring speed is 100-600 rpm, the stirring temperature is 50-90° C., and the stirring time is 5-20 minutes.
[0084] Furthermore, in step P2, the pH can be adjusted by using an acetic acid aqueous solution, and the pH value is adjusted to 2-4.
[0085] Furthermore, in step P3, the heating temperature of the asphalt is 113-183°C. The heating temperature of the soap solution is 30-60°C.
[0086] Furthermore, in step P3, the shearing is preferably performed multiple times, and more preferably 3-5 times. The shearing rate is 3000-5000 rpm for each time, and the time for each time is 2-20 minutes.
[0087] Furthermore, the mass ratio of the composite emulsifier added in step P4 to the composite emulsifier added in step P2 is 1:2-5.
[0088] Furthermore, in step P4, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes.
[0089] Furthermore, in step P5, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes.
[0090] Furthermore, in step P6, the suspending agent is preferably added in multiple times, and more preferably added in 3-5 times.
[0091] Furthermore, in step P6, the stirring speed is 700-1600 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes.
[0092] Furthermore, in step P7, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes.
[0093] Furthermore, in step P8, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes.
[0094] Furthermore, in step P9, the stirring speed is 100-600 rpm, the stirring temperature is 40-90° C., and the stirring time is 2-20 minutes.
[0095] Compared with the prior art, the present invention has the following advantages:
[0096] (1) The odorless and environment-friendly sand-containing fog seal of the present invention contains special odorless and environment-friendly microcapsules, and its composite shell material has three functions. First, during the preparation process, nano-tourmaline serves as a template for the synthesis of microcapsules, which can maintain the stability of the core material mixed droplets; second, during the metal ion modification of the microcapsule composite shell material, a large amount of metal ions are adsorbed onto the microcapsule surface by means of the negative ion field released by nano-tourmaline under high temperature conditions, effectively increasing the metal ion loading capacity of the microcapsule shell material, and further improving the smoke suppression ability of the slow-release modified microcapsules; the third function is that during the asphalt mixing process, under the action of high temperature, the nano-tourmaline contained in the slow-release modified microcapsule shell material will release a negative ion field, further attracting the compounds released by the asphalt under the action of high temperature to the vicinity of the slow-release modified microcapsules, while increasing the difficulty of these compounds volatilizing, and allowing the metal ions on the microcapsule surface and the smoke suppression active components of the microcapsule to react with more of the above-mentioned compounds, thereby effectively reducing the impact of the irritating gas released by the asphalt pavement on the human body.
[0097] (2) The odorless and environmentally friendly sand-containing mist seal of the present invention contains odorless and environmentally friendly microcapsules, and the surface of the composite shell material is modified with a layer of chelated metal ions. This layer of chelated metal ions has empty orbitals. After the odorless and environmentally friendly microcapsules enter the asphalt system, the chelated metal ions can directly accept the unshared electrons of some relatively active sulfur-containing and nitrogen-containing pollutants in the asphalt and form coordination bonds, thereby stably fixing the above-mentioned compounds on the surface of the odorless and environmentally friendly microcapsules, avoiding their high-temperature volatilization, and further quickly reducing the content of irritating gases in the asphalt flue gas.
[0098] (3) The odorless and environmentally friendly sand-containing mist seal layer of the present invention contains odorless and environmentally friendly microcapsules, which encapsulate the odorless active components with lower boiling points in the composite shell material. These active components can be slowly released from the microcapsules during the storage and construction of asphalt, thereby avoiding the problems of decreased emission reduction effect and short duration caused by the active components volatilizing at high temperatures without reacting with related components in asphalt. In addition, the odorless and environmentally friendly microcapsules added by the present invention are relatively small in size, and their outer layer is a polydopamine film that can generate a force with the polar molecules in asphalt and has good compatibility with asphalt. Therefore, after being added to asphalt, the road performance of asphalt can be effectively prevented from being affected.
[0099] (4) The environmentally friendly sand-containing mist seal layer of the present invention has odorless environmentally friendly microcapsules added thereto, which have a fragrant aroma, and the type of aroma can be adjusted according to requirements. After the environmentally friendly sand-containing mist seal layer is spread on the road surface, it can play a role in suppressing odor and enhancing fragrance, further improving the driving environment and reducing the sensory impact of the asphalt road surface on surrounding residents.
[0100] (5) The odorless and environmentally friendly sand-containing mist seal layer of the present invention has good pavement embedding ability and can effectively extend the service life of the pavement. BRIEF DESCRIPTION OF THE DRAWINGS
[0101] Figure 1 This is a scanning electron microscope image of the odorless and environmentally friendly microcapsules obtained in Example 1. DETAILED DESCRIPTION
[0102] To further illustrate the technical solution of the present invention, the present invention will be clearly and detailed described below in conjunction with embodiments.
[0103] The odorless and environmentally friendly microcapsules of the present invention are tested for morphology by scanning electron microscopy, and the acceleration voltage used is 20 kV. Since the wall material of the microcapsule is not conductive, the sample needs to be treated with gold spraying before the test.
[0104] The smoke suppression effect of the odorless and environmentally friendly sand-containing mist sealing material of the present invention is tested by a VOC detector with an FID detector and a smoke detector with an H2S electrochemical sensor.
[0105] The base asphalt used in the following examples is Sinopec Donghai Brand 70 Grade A asphalt.
[0106] Example 1
[0107] Preparation of odorless and environmentally friendly microcapsules:
[0108] S1: Nano-tourmaline with a particle size of 60 nm, octadecyltrimethylammonium chloride and formamide are stirred at a mass ratio of 1:1:20 at 180°C and 400 rpm for 5 hours, then washed with ethanol for multiple times, and vacuum dried at -30°C for 5 hours to obtain modified nano-tourmaline for later use;
[0109] S2: 2-methylundecanal, o-methoxy-p-methylbenzaldehyde, citronellol, terpineol, isoamyl benzoate, geranyl formate, 3-hydroxy-2-butanone, and irone were mixed in equal proportions, and stirred at 400 rpm for 10 minutes at 50° C. to obtain a core material mixture;
[0110] S3: Add the modified nano-tourmaline and N,N-dimethylformamide prepared in step S1 to the reaction system of step S2, wherein the mass ratio of the core material mixture, the modified nano-tourmaline and N,N-dimethylformamide is 2:1:20, and continue to stir at 400 rpm at 50°C for 5 hours;
[0111] S4: adding tetraethyl orthosilicate to the reaction system of step S3, wherein the mass ratio of the core material mixture to tetraethyl orthosilicate is 1:1, and continuing to stir at 400 rpm at 50° C. for 5 hours to obtain a Pickering emulsion;
[0112] S5: Use a peristaltic pump to slowly drop 10 wt % dilute hydrochloric acid into the reaction system of step S4 until the pH of the reaction system is 4, continue stirring at 400 rpm at 50°C for 5 hours, then stop stirring, keep the temperature unchanged and age for 24 hours, then filter and wash the solid powder in the reaction system, and vacuum dry it at -30°C for 5 hours to obtain a odorless and environmentally friendly microcapsule matrix;
[0113] S6: adding the odorless and environmentally friendly microcapsule matrix prepared in step S5 into a Tris buffer solution with a pH value of 8.5, wherein the mass ratio of the Tris buffer solution to the odorless and environmentally friendly microcapsule matrix is 60:1, and then adding dopamine hydrochloride to make the concentration of dopamine in the reaction system 5 mg / mL, stirring at a speed of 200 rpm at 25° C. for 12 hours, then stopping stirring, filtering and washing the bottom solid powder, and vacuum drying at a temperature of -30° C. for 5 hours;
[0114] S7: Ultrasonic dispersion of the solid powder obtained in step S6 in a 50wt% anhydrous copper sulfate-formamide solution, the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution being 1:20, stirring and reacting at 400 rpm and 140°C for 2 hours, after the stirring is completed, filtering, washing, and freeze-drying the solid powder to obtain a odorless and environmentally friendly microcapsule, the electron microscope image of which is shown in FIG. Figure 1 .
[0115] The preparation method of the environmentally friendly sand-containing fog seal is as follows:
[0116] P1: Add 3 parts by mass of hexadecyltrimethylammonium bromide and 3 parts by mass of sorbitan fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;
[0117] P2: Add 45 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;
[0118] P3: 50 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C were added to a colloid mill, and sheared at a speed of 4000 rpm for 5 min, and the emulsified asphalt was obtained after cyclic shearing for 3 times;
[0119] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0120] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0121] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;
[0122] P7: Add 15 parts by mass of odorless and environmentally friendly microcapsules to the system in step P6, and stir and mix at 500 rpm and 60°C for 50 minutes;
[0123] P8: Add 10 parts by mass of polyurethane latex and 10 parts by mass of carboxylated styrene butadiene latex to the system in step P7, and stir and mix at 500 rpm and 60° C. for 40 minutes;
[0124] P9: Add 30 parts by mass of quartz sand to the system of step P8, wherein the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 70%, the mass proportion of sand particles of 70-130 mesh is 20%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 10%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain an odorless and environmentally friendly sand-containing fog sealing material.
[0125] Example 2
[0126] Except that in step S2, the core material mixture is mixed with 2-methylundecanal, benzaldehyde, ionol, isobornyl alcohol, isoamyl salicylate, linalyl formate, 3-penten-2-one, and carvone in equal weight proportions, the rest is the same as in Example 1.
[0127] Example 3
[0128] Except that the amount of the odorless and environmentally friendly microcapsules used in step P7 is 5 parts by mass, the rest is the same as in Example 1.
[0129] Example 4
[0130] Except that the latex described in step P8 is 10 parts by mass of natural latex and 10 parts by mass of nitrile latex, the rest is the same as in Example 1.
[0131] Example 5
[0132] Except that the mass ratio of the core material mixed solution, the modified nano-tourmaline and the N,N-dimethylformamide in step S3 is 4:1:20, the rest is the same as that in Example 1.
[0133] Example 6
[0134] Except that the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution in step S7 is 1:15, the rest is the same as that in Example 1.
[0135] Example 7
[0136] Except that the latex described in step P8 is 5 parts by mass of natural latex and 5 parts by mass of nitrile latex, the rest is the same as Example 1.
[0137] Comparative Example 1
[0138] P1: Add 3 parts by mass of hexadecyltrimethylammonium bromide and 3 parts by mass of sorbitan fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;
[0139] P2: Add 45 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;
[0140] P3: 50 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C were added to a colloid mill, and sheared at a speed of 4000 rpm for 5 min, and the emulsified asphalt was obtained after cyclic shearing for 3 times;
[0141] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0142] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0143] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;
[0144] P7: Add 10 parts by mass of polyurethane latex and 10 parts by mass of carboxylated styrene butadiene latex to the system in step P6, and stir and mix at 500 rpm and 60° C. for 40 minutes;
[0145] P8: Add 30 parts by mass of quartz sand to the system of step P7, wherein the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 70%, the mass proportion of sand particles of 70-130 mesh is 20%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 10%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain an odorless and environmentally friendly sand-containing fog sealing material.
[0146] Comparative Example 2
[0147] Preparation of odorless and environmentally friendly microcapsules:
[0148] S1: 2-methylundecanal, o-methoxy-p-methylbenzaldehyde, citronellol, terpineol, isoamyl benzoate, geranyl formate, 3-hydroxy-2-butanone, and irone were mixed in equal proportions, and stirred at 400 rpm for 10 minutes at 50° C. to obtain a core material mixture;
[0149] S2: Add hexadecyltrimethylammonium bromide and N,N-dimethylformamide to the reaction system of step S1, the mass ratio of the core material mixture, hexadecyltrimethylammonium bromide and N,N-dimethylformamide is 5:1:20, and continue to stir at 400 rpm at 50°C for 5 hours;
[0150] S3: adding tetraethyl orthosilicate to the reaction system of step S2, with the mass ratio of the core material mixture to tetraethyl orthosilicate being 1:1, and continuing to stir at 400 rpm at 50° C. for 5 hours to obtain a Pickering emulsion;
[0151] S4: Use a peristaltic pump to slowly add 10 wt% dilute hydrochloric acid to the reaction system of step S3 until the pH of the reaction system is 4, continue stirring at 400 rpm at 50°C for 5 hours, then stop stirring, keep the temperature unchanged and age for 24 hours, then filter and wash the solid powder in the reaction system, and vacuum dry it at -30°C for 5 hours to obtain a odorless and environmentally friendly microcapsule matrix;
[0152] S5: adding the odorless and environmentally friendly microcapsule matrix prepared in S4 into a Tris buffer solution with a pH value of 8.5, wherein the mass ratio of the Tris buffer solution to the odorless and environmentally friendly microcapsule matrix is 60:1, and then adding dopamine hydrochloride to make the concentration of dopamine in the reaction system 5 mg / mL, stirring at 200 rpm for 12 hours at 25°C, then stopping stirring, filtering and washing the bottom solid powder, and vacuum drying at -30°C for 5 hours;
[0153] S6: Ultrasonic dispersion of the solid powder obtained in step S5 in a 50wt% anhydrous copper sulfate-formamide solution, wherein the mass ratio of the solid powder to the anhydrous copper sulfate-formamide solution is 1:20, and stirring the mixture at 400 rpm and 140°C for 2 hours. After stirring, the solid powder is filtered, washed, and freeze-dried to obtain odorless and environmentally friendly microcapsules.
[0154] The preparation method of the environmentally friendly sand-containing fog seal is as follows:
[0155] P1: Add 3 parts by mass of hexadecyltrimethylammonium bromide and 3 parts by mass of sorbitan fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;
[0156] P2: Add 45 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;
[0157] P3: 50 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C were added to a colloid mill, and sheared at a speed of 4000 rpm for 5 min, and the emulsified asphalt was obtained after cyclic shearing for 3 times;
[0158] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0159] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0160] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;
[0161] P7: Add 15 parts by mass of odorless and environmentally friendly microcapsules to the system in step P6, and stir and mix at 500 rpm and 60°C for 50 minutes;
[0162] P8: Add 10 parts by mass of polyurethane latex and 10 parts by mass of carboxylated styrene butadiene latex to the system in step P7, and stir and mix at 500 rpm and 60° C. for 40 minutes;
[0163] P9: Add 30 parts by mass of quartz sand to the system of step P8, wherein the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 70%, the mass proportion of sand particles of 70-130 mesh is 20%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 10%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain an odorless and environmentally friendly sand-containing fog sealing material.
[0164] Comparative Example 3
[0165] The preparation of odorless and environmentally friendly microcapsules is the same as in Example 1.
[0166] The preparation method of the environmentally friendly sand-containing fog seal is as follows:
[0167] P1: Add 3 parts by mass of hexadecyltrimethylammonium bromide and 3 parts by mass of sorbitan fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;
[0168] P2: Add 45 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;
[0169] P3: 50 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C were added to a colloid mill, and sheared at a speed of 4000 rpm for 5 min, and the emulsified asphalt was obtained after cyclic shearing for 3 times;
[0170] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0171] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0172] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;
[0173] P7: Add 15 parts by mass of odorless and environmentally friendly microcapsules to the system in step P6, and stir and mix at 500 rpm and 60°C for 50 minutes;
[0174] P8: Add 30 parts by mass of quartz sand to the system of step P7, wherein the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 70%, the mass proportion of sand particles of 70-130 mesh is 20%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 10%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain an odorless and environmentally friendly sand-containing fog sealing material.
[0175] Comparative Example 4
[0176] Preparation of odorless and environmentally friendly microcapsules:
[0177] S1: Nano-tourmaline with a particle size of 60 nm, octadecyltrimethylammonium chloride and formamide are stirred at a mass ratio of 1:1:20 at 180°C and 400 rpm for 5 hours, then washed with ethanol for multiple times, and vacuum dried at -30°C for 5 hours to obtain modified nano-tourmaline for later use;
[0178] S2: 2-methylundecanal, o-methoxy-p-methylbenzaldehyde, citronellol, terpineol, isoamyl benzoate, geranyl formate, 3-hydroxy-2-butanone, and irone were mixed in equal proportions, and stirred at 400 rpm for 10 minutes at 50° C. to obtain a core material mixture;
[0179] S3: Add the modified nano-tourmaline and N,N-dimethylformamide prepared in step S1 to the reaction system of step S2, wherein the mass ratio of the core material mixture, the modified nano-tourmaline and N,N-dimethylformamide is 2:1:20, and continue to stir at 400 rpm at 50°C for 5 hours;
[0180] S4: adding tetraethyl orthosilicate to the reaction system of step S3, wherein the mass ratio of the core material mixture to tetraethyl orthosilicate is 1:1, and continuing to stir at 400 rpm at 50° C. for 5 hours to obtain a Pickering emulsion;
[0181] S5: Use a peristaltic pump to slowly drop 10 wt % dilute hydrochloric acid into the reaction system of step S4 until the pH of the reaction system is 4, continue stirring at 400 rpm at 50°C for 5 hours, then stop stirring, keep the temperature unchanged and age for 24 hours, then filter and wash the solid powder in the reaction system, and vacuum dry it at -30°C for 5 hours to obtain a odorless and environmentally friendly microcapsule matrix;
[0182] S6: Add the odorless and environmentally friendly microcapsule matrix prepared in step S5 into a Tris buffer solution with a pH value of 8.5, wherein the mass ratio of the Tris buffer solution to the odorless and environmentally friendly microcapsule matrix is 60:1, and then add dopamine hydrochloride to make the concentration of dopamine in the reaction system 5 mg / mL. Stir at 200 rpm at 25°C for 12 hours and then stop stirring. Filter and wash the solid powder on the bottom layer, and vacuum dry it at -30°C for 5 hours.
[0183] The preparation method of the environmentally friendly sand-containing fog seal is as follows:
[0184] P1: Add 3 parts by mass of hexadecyltrimethylammonium bromide and 3 parts by mass of sorbitan fatty acid ester into the first container, and stir evenly to obtain a composite emulsifier;
[0185] P2: Add 45 parts by mass of deionized water and 5 parts by mass of the composite emulsifier prepared in step P1 into a second container, stir and mix at 60° C. and 400 rpm for 20 minutes, and adjust the pH to 3 with an acetic acid aqueous solution to obtain a soap solution;
[0186] P3: 50 parts by mass of 70#A grade asphalt heated to 163°C and the soap solution obtained in step P2 heated to 60°C were added to a colloid mill, and sheared at a speed of 4000 rpm for 5 min, and the emulsified asphalt was obtained after cyclic shearing for 3 times;
[0187] P4: Add 1 part by mass of the composite emulsifier obtained in step P2 to the emulsified asphalt obtained in step P3, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0188] P5: Add 2 parts by mass of polydimethylsiloxane to the reaction system of step P4, and stir and mix at 400 rpm and 60° C. for 20 minutes;
[0189] P6: Slowly add 30 parts by mass of 1200 mesh kaolin to the reaction system of step P5 in 5 portions, and stir and mix at 1500 rpm and 60° C. for 40 minutes;
[0190] P7: Add 15 parts by mass of the odorless and environmentally friendly microcapsule matrix to the system in step P6, and stir and mix at 500 rpm and 60°C for 50 minutes;
[0191] P8: Add 10 parts by mass of polyurethane latex and 10 parts by mass of carboxylated styrene butadiene latex to the system in step P7, and stir and mix at 500 rpm and 60° C. for 40 minutes;
[0192] P9: Add 30 parts by mass of quartz sand to the system of step P8, wherein the mass proportion of sand particles greater than or equal to 30 mesh and less than 70 mesh is 70%, the mass proportion of sand particles of 70-130 mesh is 20%, and the mass proportion of sand particles greater than 130 mesh and less than or equal to 300 mesh is 10%. Stir and mix at 600 rpm and 60°C for 20 minutes to obtain an odorless and environmentally friendly sand-containing fog sealing material.
[0193] Test Example 1
[0194] The wear of the odorless and environmentally friendly sand-containing mist seal paint wheel and the bonding strength with the base surface were tested, and the obtained data are shown in Table 1 below.
[0195] Table 1 Performance test of sand-containing fog seal
[0196] sample <![CDATA[Wet wheel wear value is / g·m -2 > 25℃ tensile strength / MPa Example 1 29.7 2.31 Example 2 29.8 2.31 Example 3 30.0 2.3 Example 4 29.9 2.3 Example 5 30.4 2.2 Example 6 29.9 2.29 Example 7 29.9 2.3 Comparative Example 1 30.5 2.19 Comparative Example 2 30.3 2.19 Comparative Example 3 71.3 1.29 Comparative Example 4 30.5 2.21
[0197] Test Example 2
[0198] The gases released by asphalt pavement under the influence of high temperature are mainly volatile organic compounds and sulfides. In order to verify the odor-free and smoke-suppressing ability of the odor-free and environmentally friendly sand-containing fog seal layer on asphalt materials, the samples prepared in the embodiments and comparative examples are sprinkled on the surface of the asphalt mixture test block. The size of the asphalt mixture test block is 10cm*10cm*3cm. The samples are further moved into a sealed container with a gas intake port and stored at a temperature of 80°C for 2 days. After the storage is completed, the gas in the sealed container is absorbed, and the VOCs and H2S contents in the gas are tested using a VOC detector and a smoke detector. The obtained data are shown in Table 2 below.
[0199] Table 2 Asphalt smoke test data
[0200] Test samples FID test value / ppm <![CDATA[H2S test value / ppm]]> Base asphalt 89.3 26.6 Example 1 36.3 8.1 Example 2 36.4 8.2 Example 3 40.2 9.1 Example 4 36.4 8.2 Example 5 37.6 8.6 Example 6 41.5 9.6 Example 7 41.2 9.3 Comparative Example 1 89.2 26.4 Comparative Example 2 66.3 17.6 Comparative Example 3 45.6 10.9 Comparative Example 4 59.2 15.6
[0201] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A odorless and environmentally friendly sand-containing fog seal, characterized by: The odorless and environmentally friendly sand-containing fog seal layer comprises the following components in parts by mass: Asphalt: 35-70 parts; Water: 30-70 parts; Composite emulsifier: 2-8 parts; Defoaming agent: 0.5-3 parts; Latex: 5-30 parts; Suspension: 20-40 parts; Fine sand: 20-45 parts; Odor-free and environmentally friendly microcapsules: 5-40 portions; The deodorizing and environmentally friendly microcapsule comprises a composite shell material and a core material, wherein the composite shell material comprises an inorganic base shell / nano-tourmaline / polydopamine, and the core material comprises one or more deodorizing agents; and the surface of the shell material is loaded with a metal chelate.
2. The odorless and environmentally friendly sand-containing fog seal according to claim 1 is characterized by: The composite emulsifier comprises a cationic emulsifier and an amphoteric emulsifier; the mass ratio of the cationic emulsifier to the amphoteric emulsifier is 1:0.5-2.
5.
3. The odorless and environmentally friendly sand-containing fog seal according to claim 2 is characterized in that: The cationic emulsifier includes one or more of amine salt surfactants with a carbon number greater than 8; preferably, tetradecyl-dimethylpyridinium ammonium bromide, octadecyl amidopropyl dimethyl dihydroxypropyl ammonium chloride, behenic acid amidopropyl dimethyl dihydroxypropyl ammonium chloride, hexadecyl amidopropyl trimethyl ammonium chloride, dioctadecyl-methyl benzyl ammonium chloride, dodecyl dimethyl benzyl ammonium chloride, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, hexadecyl trimethyl ammonium bromide, hexadecyl trimethyl ammonium chloride, and more preferably, hexadecyl trimethyl ammonium bromide; And / or, the amphoteric emulsifier is a polyol-type surfactant; preferably one or more of fatty acid ethylene glycol esters, monoglycerides, pentaerythritol fatty acid esters, sorbitan fatty acid esters, and sucrose fatty acid esters; more preferably sorbitan fatty acid esters.
4. The odorless and environmentally friendly sand-containing fog seal according to claim 1 is characterized in that: The defoaming agent is one or more of sunflower oil, polydimethylsiloxane, eicosanol, and docosanol; And / or, the latex is one or more of natural latex, carboxylated styrene butadiene latex, polyurethane latex, nitrile latex, and chloroprene latex; And / or, the suspending agent is one or more of bentonite, kaolin, carbon black, and talc; And / or, the fine sand particles are one or more of quartz sand, carborundum, corundum sand or basalt sand.
5. The odorless and environmentally friendly sand-containing fog seal according to claim 1 is characterized in that: The particle size of the odorless and environmentally friendly microcapsules is 1-5 μm.
6. The odorless and environmentally friendly sand-containing fog seal according to claim 1 is characterized in that: The mass ratio of the odorless and environmentally friendly microcapsule composite shell material to the core material is 1:0.5-2.
7. The odorless and environmentally friendly sand-containing fog seal according to claim 1 is characterized in that: The deodorant is one or more of aldehydes, alcohols, esters, and ketones, preferably including aldehydes, alcohols, esters, and ketones at the same time; Preferably, the aldehydes are selected from one or more of aliphatic aldehydes having a carbon number greater than 10 and aromatic aldehydes having a carbon number greater than 7; the aliphatic aldehydes having a carbon number greater than 10 are selected from one or more of 2-methylundecylaldehyde and 10-undecenal; the aromatic aldehydes having a carbon number greater than 7 are selected from one or more of benzaldehyde, cinnamaldehyde, o-methoxy-p-methylbenzaldehyde, 2-methyl-3-(4-isopropylphenyl)propanal, and 2-methyl-3-(3,4-methylenedioxyphenyl)propanal; Preferably, the alcohol is selected from one or more of terpene alcohols with a carbon number greater than 10 and cyclic terpene alcohols with a carbon number greater than 10; the terpene alcohols with a carbon number greater than 10 are selected from one or more of geraniol, linalool, citronellol, ionol, farnesol, myrcenol, lavandulol, and nerolidol; the cyclic terpene alcohols with a carbon number greater than 10 are selected from one or more of menthol, terpineol, isobornyl alcohol, cedarwood alcohol, and santalol; Preferably, the esters are selected from one or more of aromatic esters having a carbon number greater than 12 and terpene esters having a carbon number greater than 11; the aromatic esters having a carbon number greater than 12 are selected from one or more of isoamyl benzoate, benzyl benzoate, isoamyl salicylate, benzyl salicylate, leaf alcohol salicylate, benzyl cinnamate, and phenylethyl cinnamate; the terpene esters having a carbon number greater than 11 are selected from one or more of geranyl formate, geranyl acetate, geranyl propionate, neryl acetate, linalyl formate, linalyl propionate, lavender acetate, and citronellal butyrate; Preferably, the ketones are selected from one or more of aliphatic ketones having a carbon number greater than 3 and cyclic terpene ketones having a carbon number greater than 10; the aliphatic ketones having a carbon number greater than 3 are selected from one or more of 3-hydroxy-2-butanone, 2,3-butanedione, and 3-pentene-2-one; the cyclic terpene ketones having a carbon number greater than 10 are selected from one or more of damascenone, ionone, irone, menthone, and carvone.
8. The odorless and environmentally friendly sand-containing fog seal according to claim 1 is characterized by: The composite shell material comprises an inorganic base shell / nano-tourmaline / polydopamine, wherein the mass ratio of the inorganic base shell to the nano-tourmaline is 1-5:1, and the mass ratio of the inorganic base shell to the polydopamine is 1:0.1-1.
9. The odorless and environmentally friendly sand-containing fog seal according to claim 1, characterized in that: The material of the inorganic base shell is selected from silicon dioxide and titanium dioxide, preferably silicon dioxide.
10. The odorless and environmentally friendly sand-containing fog seal layer according to claim 1 is characterized in that: The surface of the composite shell material is loaded with a metal chelate, wherein the metal is preferably copper; the metal loading accounts for 0.1wt%-10wt% of the total mass of the odorless and environmentally friendly microcapsule.
11. The odorless and environmentally friendly sand-containing fog seal layer according to claim 1, characterized in that: The method for preparing the odorless and environmentally friendly microcapsules comprises the following steps: S1: mixing nano-tourmaline, a surfactant and a solvent, modifying the mixture under stirring, washing the mixture after the modification, and freeze-drying the mixture to obtain modified nano-tourmaline; S2: stirring and mixing one or more deodorizing agents to obtain a core material mixed liquid; S3: adding a solvent and the modified nano-tourmaline obtained in step S1 to the core material mixed solution obtained in step S2, and stirring and mixing; S4: adding an inorganic base shell precursor to the reaction system of step S3, stirring and mixing, and obtaining a Pickering emulsion; S5: adjusting the pH value of the Pickering emulsion obtained in step S4 to 3-6, continuing stirring, and then aging, filtering, and freeze-drying to obtain a odorless and environmentally friendly microcapsule matrix; S6: dispersing the odorless and environmentally friendly microcapsule matrix obtained in step S5 in a buffer solution, adding dopamine hydrochloride, treating under stirring, and then filtering, washing, and freeze-drying; S7: dispersing the solid powder obtained after freeze-drying in step S6 in a metal ion salt-formamide solution, treating under stirring, and after the reaction is completed, filtering, washing, and freeze-drying to obtain odorless and environmentally friendly microcapsules.
12. The odorless and environmentally friendly sand-containing fog seal layer according to claim 11, characterized in that: In step S1, the surfactant is a cationic surfactant, preferably at least one of hexadecyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride, and octadecyltrimethylammonium chloride; in step S1, the solvent is an aprotic solvent with a boiling point > 100°C, preferably at least one of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide; And / or, in step S1, the mass ratio of the nano-tourmaline to the surfactant is (1-10):1, and the mass ratio of the solvent to the surfactant is (10-40):
1.
13. The odorless and environmentally friendly sand-containing fog seal layer according to claim 11, characterized in that: In step S1, the stirring speed is 400-600 rpm; the modification temperature is 100-190° C., and the modification time is 4-8 hours; And / or, in step S2, the stirring speed is 400-600 rpm, the stirring temperature is 30-70° C., and the stirring time is 3-10 minutes; And / or, in step S3, the stirring speed is 400-600 rpm, the stirring temperature is 30-60° C., and the stirring time is 4-6 hours; And / or, in step S4, the stirring speed is 400-600 rpm, the stirring temperature is 30-60° C., and the stirring time is 4-6 hours; And / or, in step S5, the stirring speed is 400-600 rpm, the stirring temperature is 30-60° C., and the stirring time is 4-6 hours; And / or, in step S6, the stirring speed is 100-300 rpm, the stirring temperature is 20-40° C., and the stirring time is 12-24 hours; And / or, in step S7, the stirring speed is 200-450 rpm, the treatment temperature is 100-190° C., and the treatment time is 2-5 hours.
14. The odorless and environmentally friendly sand-containing fog seal layer according to claim 11, characterized in that: In step S3, the solvent is an aprotic solvent with a boiling point > 100° C., preferably at least one of formamide, N,N-dimethylformamide, dimethylacetamide, and dimethylphosphoramide; And / or, in step S3, the mass ratio of the core material mixture to the modified nano-tourmaline is (1-10):1, and the mass ratio of the solvent to the modified nano-tourmaline is (10-40):
1.
15. The odorless and environmentally friendly sand-containing fog seal layer according to claim 11, characterized in that: In step S4, the inorganic base shell precursor is one of a silicate compound and a titanate compound, and is more preferably a silicate compound; And / or, the silicate compound is preferably one or more of methyl silicate, ethyl orthosilicate, tetraethyl orthosilicate, and butyl orthosilicate, and is further preferably tetraethyl orthosilicate; And / or, in step S4, the mass ratio of the core material mixture to the inorganic base shell precursor is (0.5-2):
1.
16. The odorless and environmentally friendly sand-containing fog seal layer according to claim 11, characterized in that: In step S6, the buffer solution is one or more of a phosphate buffer solution, a carbonate buffer solution, and a tris(hydroxymethyl)aminomethane hydrochloride buffer solution, preferably a tris(hydroxymethyl)aminomethane hydrochloride buffer solution; the pH value of the buffer solution is preferably 8-10; And / or, in step S6, the mass ratio of the buffer solution to the odorless and environmentally friendly microcapsule matrix obtained in step S5 is (10-100):
1.
17. The odorless and environmentally friendly sand-containing fog seal layer according to claim 11, characterized in that: In step S6, after adding dopamine hydrochloride, the mass concentration of dopamine in the reaction system is 2-10 mg / mL.
18. The odorless and environmentally friendly sand-containing fog seal layer according to claim 11, characterized in that: In step S7, the metal ion salt is preferably a copper ion salt, and more preferably anhydrous copper sulfate; in the metal ion salt-formamide solution, the mass ratio of the metal ion salt to formamide is (0.5-1.5):1; the mass ratio of the metal ion salt-formamide solution to the solid powder obtained after freeze-drying in step S7 is (5-20):
1.
19. A method for preparing the odorless and environmentally friendly sand-containing fog seal according to any one of claims 1 to 18, characterized in that: The steps include: P1: Preparation of composite emulsifier; P2: Stir and mix water and part of the composite emulsifier prepared in step P1, adjust the pH value, and obtain a soap solution; P3: After heating the asphalt and the soap solution obtained in step P2 respectively, shearing them to obtain emulsified asphalt; P4: Add the remaining part of the composite emulsifier prepared in step P1 to the emulsified asphalt obtained in step P3, and stir to mix; P5: Add defoaming agent to the reaction system of step P4 and stir to mix; P6: Add a suspending agent to the reaction system of step P5 and stir to mix; P7: Add the odorless and environmentally friendly microcapsules to the reaction system of step P6 and stir to mix; P8: Add latex to the reaction system in step P7 and stir to mix; P9: Add fine sand particles to the reaction system of step P8, stir and mix, and obtain an odorless and environmentally friendly sand-containing fog seal layer.
20. The preparation method according to claim 19, characterized in that: In step P2, the stirring speed is 100-600 rpm, the stirring temperature is 50-90° C., and the stirring time is 5-20 minutes; And / or, in step P4, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes; And / or, in step P5, the stirring speed is 100-600 rpm, the stirring temperature is 30-90° C., and the stirring time is 2-20 minutes; And / or, in step P6, the stirring speed is 700-1600 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes; And / or, in step P7, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes; And / or, in step P8, the stirring speed is 300-500 rpm, the stirring temperature is 30-90° C., and the stirring time is 10-50 minutes; And / or, in step P9, the stirring speed is 100-600 rpm, the stirring temperature is 40-90° C., and the stirring time is 2-20 minutes.
21. The preparation method according to claim 19, characterized in that: In step P2, the pH is adjusted by using an acetic acid aqueous solution, and the pH value is adjusted to 2-4.
22. The preparation method according to claim 19, characterized in that: The mass ratio of the composite emulsifier added in step P4 to the composite emulsifier added in step P2 is 1:2-5.